Tradition et évolution dans l’art du Powwow contemporain - Jeanine Belgodère (Revue LISA)
Inter-tribal Powwows, most of which feature dance contests, are both a social gathering and an artistic performance. Primarily designed to preserve and to continue the spiritual and communal values inherent in Native American culture, they contribute to strengthening the bond of friendship between all tribes and ultimately to reunifying the circle. This deep sense of cultural belonging is essentially conveyed through dance where tradition and modernity interact. Evolving over decades, dance has undergone significant changes which mirror a moving identity. This is also noticeable in the women’s dances, a possible reflection of the evolution of the relations between men and women. If the so-called traditional dances such as the Grass Dance reveal a less significant mix of tribal styles, others such as the Fancy Dance — one of the newest — would tend to reflect a more homogeneous identity. Indeed, the Fancy Dance integrates some steps and elements of the dress belonging to a greater number of tribes into the style. Therefore it welcomes diversity within unity. On the whole, inter-tribal Powwows have become a medium for the pantribal expression of Indian identity. Within the context of panindianism as well as competition, might the spiritual values and the unique traits of the various dances handed down generations be jeopardized?